Weeds, Roads and God A Half-Century of Culture Change among the Philippine Ga'dang - Wallace, Ben J. 1937- (Long Grove, Illinois Waveland Press, Inc., 2013)
"Anthropology has a prominent history among the hill peoples of the Philippines, as chronicled by the discipline's pioneers who conducted research in Luzon, the largest archipelago in the Philippines and home to minority indigenous tribes, including the Ga'dang. In Weeds, Roads, and God, seasoned ethnographer Ben Wallace offers readers a blend of empirical and interpretative data from his original fieldwork among the Ga'dang in the mid-sixties and his follow-up study nearly a half-century later. With considerable authority and insight, Wallace documents this people's remarkable adaptation and longitudinal response to environmental, social, economic, and spiritual change over a period of almost fifty years--something few ethnographers have accomplished."--Back cover.
Includes bibliographical references (pages 153-160).
Keywords: Gaddang (Philippine people); Ethnology -- Philippines